Design of Instagram Aksesmu Content as a Promotional Medium at PT Sumber Trijaya Lestari - Syfa Faizah Neldillah; Bangkit Sanjaya (International Journal Labs, 2026)
The development of social media, particularly Instagram, encourages companies to optimize visual content as a medium for digital information dissemination and promotion. PT Sumber Trijaya Lestari, through the Aksesmu platform, utilizes the Instagram account @aksesmu.id to deliver information regarding products, services, promotions, and educational content to micro, small, and medium enterprise (MSME) actors, particularly stall and grocery store owners. However, the visual presentation of the content currently used still requires optimization in several aspects, particularly layout composition, typographic hierarchy, color application, and visual consistency. This research aims to design Instagram Aksesmu content as an information and promotional medium by applying visual communication design principles that align with the brand identity and characteristics of the target audience. The research method used was qualitative, involving observations of the Instagram account @aksesmu.id, interviews with the Marketing Communication division of PT Sumber Trijaya Lestari, documentation, and literature studies. The design outcomes include Instagram feed designs and Reels cover designs that apply a simple, communicative, informative, and consistent visual approach. The application of design elements, including color schemes, layouts, typography, illustrations, and visual hierarchy, helps improve message delivery clarity and strengthens Instagram’s role as an information and promotional medium. Therefore, the design of Instagram Aksesmu content can serve as an alternative approach for developing digital visual communication that is more structured, accessible, and aligned with the company’s communication needs.